Potensi Karbon Biru Kepulauan Dan Akuntansi Blockchain: Studi Literatur - Malawat, Fadli Fendi; Hamizar, Arizal; Hanifah, Hanifah; Buton, Farly; Kelarat, Almi Saputra; Fitri, Wa Ode (LPPM POLITEKNIK LP3I BANDUNG, 2026)
This study aims to systematically examine several scientific works related to blue carbon accounting in archipelagic regions and to explore the potential use of blockchain technology as an innovative solution for decentralized, transparent, and participatory carbon reporting. This study adopts a conceptual synthesis approach, The research also employs a Systematic Literature Review (SLR) method, analyzing 11 selected articles from databases such as Scopus, Web of Science, ScienceDirect, DOAJ, and Google Scholar, published between 2014 and 2024. The findings reveal that although blue carbon ecosystems hold significant economic and ecological value, carbon reporting remains dominated by top-down approaches, with limited involvement of local stakeholders. Meanwhile, blockchain technology shows promise in addressing reporting challenges through a distributed ledger system, automated verification via smart contracts, and token-based incentive schemes. The study concludes that integrating blockchain into blue carbon accounting could enhance accountability, efficiency, and equity in carbon reporting. It also recommends conducting further empirical research within the Indonesian archipelagic context to validate these findings.